Kinerja Forum Ekonomi Syariah Program Studi Perbankan Syariah FAI UNISMA Bekasi dalam Meningkatkan Kualitas Sumber Daya Insani Perbankan Syariah - Abdul Khoir (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This research aims to determine the performance of Sharia Economic Forum(FOREKS) as the association of student Departement of Sharia Banking, IslamicStudies of UNISMA Bekasi in in improving the quality of human resources ofIslamic banking. This research uses qualitative method. The conclusion of thisresearch that the performance of Sharia Economic Forum is supportive in improvingthe quality of human resources of its members, such as giving the nuance ofdiscipline in the organization and teaches the adaptability with new environmentand teaches professionalism in performing duties and functions as board andmembers of Sharia Economic Forum. As for the inhibiting factors of the ShariaEconomic Forum in improving the quality of human resources of its members, thatmonotonous and boring activity is almost felt by all members, so many memberswho choose not to play an active role even seem to consider the Sharia EconomicForum only a formality.